Anticipatory and Stimulus-Evoked Blood Oxygenation Level-Dependent Modulations Related to Spatial Attention Reflect a Common Additive Signal - Sylvester, Chad M. (Society for Neuroscience, 2009)
Covert attention is associated with prestimulus blood oxygenation level-dependent (BOLD) modulations in visual cortex. In some situations, this preparatory activity can predict how well human subjects will perceive upcoming visual objects. Preparatory activity may mediate this behavioral effect by affecting the stimulus-evoked response, but the relationship between preparatory and stimulus-evoked BOLD modulations is unclear. Here, we examine this relationship by comparing the effects of spatial attention on anticipatory and stimulus-evoked signals and by measuring the trial-to-trial correlation between prestimulus and poststimulus modulations. We find that in extrastriate visual cortex (V4), modulations related to spatial attention are relatively large, extend from prestimulus through the peak of the evoked response, and are slightly larger in the evoked response compared with the prestimulus response. In striate cortex (V1), the frontal eye fields (FEF), and the intraparietal sulcus (IPS), modulations related to spatial attention are relatively small, are confined primarily to the prestimulus period, and are slightly larger in preparatory versus stimulus-evoked activity. Importantly, across visual cortex, the attentional biases (activity for attended versus unattended locations) in preparatory and evoked activity are more positively correlated, trial-by-trial, than would be expected on the basis of activity measured in subjects at rest. We argue that this pattern of results suggests that the same mechanisms underlie preparatory and stimulus-evoked BOLD modulations related to spatial attention and that incoming sensory signals add to preexistent biases in preparatory activity to generate the stimulus-evoked response.